The degree of practice of school principals in the Northern Mazar district of administrative performance from the point of view of the female teachers - Alali, Tahani Ibrahim (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of practice of school principals in the Northern Mazar district of administrative performance from the point of view of the female teachers. The study adopted the descriptive approach, and the researcher developed a questionnaire of (22) phrases distributed to a random sample of (225) female teachers, at a rate of (40%). From the study population of (557) female teachers, and the results of the study showed that the degree of administrative performance practice obtained a total average (3.05 of it), that is, with a (medium) degree of practice. The arithmetic averages of the phrases ranged between (3.30 - 264), all of them with a (medium) degree; The results also revealed that there were no statistically significant differences in the degree of administrative performance practice due to the variables (school stage, years of experience, and educational qualification).Based on the results, the researcher recommended holding Training workshops that help school administrations develop the practice of administrative performance with all motivation and high efficiency, raise the level of school performance and achieve its goals, spread the culture of administrative performance practice and its importance in schools in achieving educational goals. More studies and research on topics related to the dimensions of administrative performance.